2021
DOI: 10.1007/s00421-021-04626-3
|View full text |Cite
|
Sign up to set email alerts
|

Individual characteristics associated with the magnitude of heat acclimation adaptations

Abstract: Purpose The magnitude of heat acclimation (HA) adaptations varies largely among individuals, but it remains unclear what factors influence this variability. This study compared individual characteristics related to fitness status and body dimensions of low-, medium-, and high responders to HA. Methods Twenty-four participants (9 female, 15 male; maximum oxygen uptake [$$\dot{{V}}$$ V ˙ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Large observed variability in PVE -both between and within individuals -is common in short term HA studies, where the variation in the response can equal the magnitude of the average change (Garrett et al, 2012(Garrett et al, , 2014Graham et al, 2016;Pethick et al, 2018;Racinais et al, 2012;Willmott et al, 2017). Individual factors such as fitness, baseline Hct, previous heat exposure and body dimensions may partly explain variation in the PVE response (Alkemade et al, 2021;Corbett et al, 2018). However, the modulating factors of individual variation to HA are still largely unresolved (Corbett et al, 2018), particularly in designs conducive to such conclusions (Atkinson & Batterham, 2015;Atkinson et al, 2019).…”
Section: Plasma Volume Expansionmentioning
confidence: 99%
“…Large observed variability in PVE -both between and within individuals -is common in short term HA studies, where the variation in the response can equal the magnitude of the average change (Garrett et al, 2012(Garrett et al, , 2014Graham et al, 2016;Pethick et al, 2018;Racinais et al, 2012;Willmott et al, 2017). Individual factors such as fitness, baseline Hct, previous heat exposure and body dimensions may partly explain variation in the PVE response (Alkemade et al, 2021;Corbett et al, 2018). However, the modulating factors of individual variation to HA are still largely unresolved (Corbett et al, 2018), particularly in designs conducive to such conclusions (Atkinson & Batterham, 2015;Atkinson et al, 2019).…”
Section: Plasma Volume Expansionmentioning
confidence: 99%
“…Energy intake is an outcome subject to a high degree of interindividual variability [44][45][46]. As thermal stress is also experienced very differently between individuals [47][48][49] and physiological and perceptive markers may be very weakly associated [50,51], we expected to find inconsistent effects of heat and cold exposures on energy intake. However, despite all these limitations, we found that exposures to heat and cold had clear effects, as the changes in energy intake were small-to-modest but appear robust under the circumstances.…”
Section: Discussionmentioning
confidence: 97%
“…The precise reason for the observed inter-individual variability in response to HA is difficult to determine. It could relate to an individualised genetic or phenotypic characteristics that modulate the magnitude of the response to HA adaptation (Taylor 2014 ; Corbett et al 2018 ; Alkemade et al 2021 ). Conceivably, some athletes or coaches may consider short-term HA training an acceptable risk to obtain a possible performance advantage.…”
Section: Discussionmentioning
confidence: 99%